The Role of Entrapment in Crisis-Focused Psychotherapy Delivered in Psychiatric Emergency Settings: A Comparative Study - Tzur Bitan, Dana; Otmazgin, Adi; Shani Sela, Mirit; Segev, Aviv (Frontiers in Psychology, 2019)
Although many mental health centers offer crisis intervention services as part of their psychiatric emergency facilities, studies assessing outcome and process of crisis intervention psychotherapy are scarce. One potential mechanism that might be unique to crisis intervention psychotherapy is entrapment, a psychological construct which reflects an individual’s subjective perception of being in uncontrollable, unremitting, and inescapable circumstances. In this study we aimed to investigate whether changes in entrapment affect the process and outcome of crisis intervention psychotherapy, as compared to its effect in short-term psychotherapy delivered in outpatient units. Sixty-nine patients were recruited for the study. Patients were assessed for level of entrapment, symptoms, well-being, and the working alliance at three time points. The moderating effect of the type of therapy on the associations between changes in entrapment and changes in symptoms, well-being and the working alliance were assessed using the Hayes process script. The dynamics of change following crisis intervention psychotherapy, as well as the effect of changes in entrapment on symptomatic relief, were illustrated using a clinical vignette of a patient treated in the crisis unit. Results of the moderation analyses indicated that entrapment had a more substantial effect on symptom distress in crisis intervention psychotherapy as compared to its effect in the short-term psychotherapy. Further, the difference in the effect of entrapment across the study groups was manifested primarily in internal entrapment, whereas no moderating effect was found for external entrapment. Clinical vignettes demonstrated the dynamics through which crisis intervention psychotherapy produces changes in entrapment by offering potential outlets from internal thoughts and interpretations of life circumstances. These results suggest that entrapment is a potential underlying process unique to crisis intervention psychotherapy. Limitations, directions for future research, and clinical implications are discussed.